دراسة وتصميم منظومة ميكاترونيكية لمساعدة المكفوفين في التعرف على الأشكال - حاتم إياد; خلاص طارق (Latakia University Journal -Engineering Sciences Series, 2018)
This research aims to study and design a mechatronic system capable of rendering images through a touchable surface to help the blind to read and understand these images. This system uses mechanical and electronic techniques and integrated software to convert the gray image to a three-dimensional surface. The mechanical mechanisms used with the control systems have been studied to reach the design that is capable of transferring the fixed images to the mechanical system with the possibility of forming surfaces with suitable accuracy. The gray levels in the stationary images were represented as a mathematical variable that changes on the Z axis in terms of Cartesian coordinates where zero is considered black, and the maximum value expresses the white and gray levels within the linear area of these two points The “Afroge” image processing library was used with the C# programming language to build an interface for analysis and communication with the Arduino controllers, which acted as an intermediary to link the image data and the mechanical device (tactile display) to display images for the blind. Finally all designed systems (mechanical, electronic and software) have been tested after they have been successfully designed. Training of a group of blind people was conducted to test the system on several samples of images of different forms and the system has demonstrated its ability to transmit multiple types of information. يهدف هذا البحث إلى تصميم منظومة ميكاترونيكية قادرة على تشكيل الصور الرمادية على مجسم ميكانيكي لمساعدة المكفوفين في التعرف على تلك الصور. تستخدم المنظومة تقنيات ميكانيكية والكترونية وبرمجية متكاملة لتحقيق العمل بشكل فعال وقابل للتنفيذ ، حيث تم دراسة الآليات الميكانيكية المستخدمة مع منظومات التحكم للوصول الى التصميم القادر على نقل الصور الثابتة إلى المنظومــة الميكانيكيــة بالإضافة إلى إمكانية تشكيل توابع رياضية في فضائين ثنائي وثلاثي البعد. مثلت السويات الرمادية في الصور الثابتة عن طريق تابع رياضي خطي يتغير على المحور Z حسب الإحداثيات الديكارتية حيث تم اعتبار نقطة الـ 0 هي اللون الأسود والنقطة النهائية تعبر عن اللون الأبيض على خلاف السويات الرمادية الواقعة ضمن المجال الخطي لهاتين النقطتين. وباستخدام مكتبات معالجة الصور Aforge في لغة البرمجة C# تم بناء واجهة للتحليل والتخاطب مع متحكمات الأوردوينو Arduino والتي هي اللاعب الأساسي والوسيط للربط بين بيانات الصور Image data والجهاز الميكانيكي (الشاشة اللمسية) لعرض الصور للكفيف. أخيرا اختبرت كل المنظومات المصممة (الميكانيكية والإالكترونية والبرمجية) بعد الإنتهاء من تصميمها ، كما وأجري تدريب لبعض المكفوفين للتعامل مع الشكل الناتج لتجربة أداء هذه الخوارزميات وبعد تقييم الأداء للجهاز أظهر قدرته في نقل أنواع متعددة من المعلومات.